Optimum Rotation Speed for the Friction Stir Welding of Pure Copper. (6th August 2013) - Jabbari, Masoud; Tutum, Cem C.
Abstract : The friction stir welding (FSW) was conducted in the pure copper plates with the thickness of 4 mm in the constant traverse speed of 25 mm/min and five different rotation speeds. Analysis of metallographic images showed that the increasing of the rotation speed results in the increase of grain size in the nugget zone. Vickers hardness tests were conducted on the weld samples and the maximum hardness obtained in rotation speed of 900 rpm. Results of the tensile tests and their comparison with that of the base metal showed that the maximum strength and the minimum elongation are achieved again in this rotation speed. Yield strength and ultimate tensile strength increased with the decrease in grain size in the nugget region, and the yield strength obeyed σ s = 172.77 + 59.33 d − 1 / 2 Hall-Petch relationship. Hence, the hardness values do not follow the relationship.